If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5y + -7)(2y + 8) = 0 Reorder the terms: (-7 + 5y)(2y + 8) = 0 Reorder the terms: (-7 + 5y)(8 + 2y) = 0 Multiply (-7 + 5y) * (8 + 2y) (-7(8 + 2y) + 5y * (8 + 2y)) = 0 ((8 * -7 + 2y * -7) + 5y * (8 + 2y)) = 0 ((-56 + -14y) + 5y * (8 + 2y)) = 0 (-56 + -14y + (8 * 5y + 2y * 5y)) = 0 (-56 + -14y + (40y + 10y2)) = 0 Combine like terms: -14y + 40y = 26y (-56 + 26y + 10y2) = 0 Solving -56 + 26y + 10y2 = 0 Solving for variable 'y'. Factor out the Greatest Common Factor (GCF), '2'. 2(-28 + 13y + 5y2) = 0 Factor a trinomial. 2((-4 + -1y)(7 + -5y)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-4 + -1y)' equal to zero and attempt to solve: Simplifying -4 + -1y = 0 Solving -4 + -1y = 0 Move all terms containing y to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -1y = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -1y = 0 + 4 -1y = 0 + 4 Combine like terms: 0 + 4 = 4 -1y = 4 Divide each side by '-1'. y = -4 Simplifying y = -4Subproblem 2
Set the factor '(7 + -5y)' equal to zero and attempt to solve: Simplifying 7 + -5y = 0 Solving 7 + -5y = 0 Move all terms containing y to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -5y = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -5y = 0 + -7 -5y = 0 + -7 Combine like terms: 0 + -7 = -7 -5y = -7 Divide each side by '-5'. y = 1.4 Simplifying y = 1.4Solution
y = {-4, 1.4}
| 61h=3.2-3.2h | | -5m+7(8-11m)=-94-7 | | 4x-9/2=8 | | 7x-(11x^2+9x)= | | 2x+21-x+21=2 | | y=-0.00211x^2+1.06x | | 9x^2+9y^2+6x-12y+1=0 | | 6-m/6-1=0 | | -22=22-5x | | 6-m/6-1=2 | | x^2+-6x+99=121 | | 80.25-70.25= | | d/dx(ln(e^2x))) | | X/6(-9)=3 | | 5.5/22 | | 5000=0.15+250n | | 33=-3(x-7) | | 21=0.75 | | 0.15=250x+5000 | | 4=7x+-8+-3x | | P+258=-4p+8 | | 42=5x+8 | | 4(x-2)2=36 | | 2000+x=3300-0.15 | | 7(2-7x)=259 | | (8w+4x)(5w-6x)=0 | | 2000+x=3300+0.15 | | Y-25=3y+5 | | 13-7r=24 | | 15=3t-5-8t | | (15mn)(-4m+6mn-10n)= | | y-1=3/4(x-2) |